Shear behavior and dilatancy of an artificial hard-matrix bimrock: An experimental study focusing on the role of blocky structure - Amir Yazdani; Saeed Karimi-Nasab; Hossein Jalalifar (Rock Mechanics Bulletin, 2024)
Bimrocks are characterized by their geotechnically significant blocky structure, presenting complex shear behavior. This study investigates the shear behavior and dilatancy of bimrocks featuring a rock-like matrix, such as conglomerates. The study addresses a gap in current research, which has predominantly examined the shear behavior of soil-matrix bimrocks (bimsoils). Laboratory direct shear tests were performed on idealized models with varying volumetric block proportions (VBPs). The results highlight that blocks exert both positive and negative effects on shear strength, dilation, and block breakage factor (BF), depending on VBP. Results indicate 40% and 60% as critical VBPs, revealing distinct shear strength trends within this range, contrary to the dominant downward trend. Blocks positively impact dilation and BF between 20% and 50% VBP, while negatively affecting them beyond this range. Blocky skeleton inherently promotes stable dilatancy under normal stress increments and intensifies stress dependency of shear strength. Variations in dilation angle concerning normal stress and VBP suggest the potential for characterizing this factor using equivalent strength and roughness, akin to rockfill materials. Indirect assessments of equivalent strength revealed positive effects of blocks when VBP was between 30% and 70%. Lastly, the findings indicate that blocks notably impact pre- and post-peak behaviors by reducing shear stiffness and inducing local hardening phases. This study also discusses the similarities and distinctions in the function of blocks within soil-like and rock-like matrices. It offers new insights into the exact role of blocks in bimrock shear behavior beyond the traditional interpretation through the variation of friction and cohesion.